Attitudes towards entrepreneurship education: a comparative analysis - David Pickernell (Education + Training, 2010)
This paper aims to examine the impact of enterprise education on entrepreneurial attitude within European higher education institutions (HEIs) in France, Germany and Poland. The research seeks to consider whether differences between cultural and industrial heritage can influence entrepreneurial attitude and mediate the effectiveness of enterprise education. Research argues that Europe requires more entrepreneurs willing to innovate and create new ventures to facilitate economic growth. This research builds on prior studies, which have examined the impact of enterprise education and training on business start‐up. In particular the study utilises the concept of entrepreneurial attitude to measure how enterprise education influences students' perceptions of, and motivations towards, entrepreneurship as a viable career option. The study contrasts and compares the impact of a short enterprise course on entrepreneurial attitude among undergraduate students in French, German and Polish HEIs. A quantitative methodology employed a research instrument utilising five‐point Likert arrays to contrast attitudes and opinions of students both prior to, and after, the delivery of the course. Enterprise education has a positive impact on entrepreneurial attitude of French and Polish students. Conversely, the course had a negative impact on male German students. It was also found that while female students are more likely to perceive a greater benefit from the learning experience, the impact of enterprise education on entrepreneurial attitude is actually more significant for male students. The research findings are of interest to academia and policy makers. The study suggests that entrepreneurial attitude among European students can be influenced by exposure to enterprise education. The results also indicate that gender, cultural and industrial heritage can moderate the impact of enterprise education. The paper provides evidence that differences between gender, culture and regional settings need to be considered in the design and delivery of enterprise programmes if they are to have the desired impact on entrepreneurial intent and graduate entrepreneurship.